Polimorfismos moleculares da praga da cana-de-açúcar Migdolus sp. (COLEOPTERA; VESPERIDAE) - Ruiz, Juliana Bueno (2011)
Migdolus is a beetle of Vesperidae family whose larval stage damages the root system of sugar cane. The losses caused by this insect can vary from a few tons of cane per hectare up to, in most cases, the complete destruction of the crop, resulting in early retirement even sugar cane fields in addition to the first cut. Beyond the normal difficulties of any pest control soil, ignorance of the various phases of the cycle of this beetle species further complicates his match. Thus, this study aimed to biochemical characterization the esterases and total proteins, standardize protocols for isolation of total DNA and PCR primers for RAPD and verify the genetic variability and population structure of Migdolus sp. four populations from the northwestern region of Paraná. Migdolus sp. adults were collected in Umuarama, Cidade Gaucha, Colorado and Tapejara. Analyses of isozymes and total protein were performed by PAGE electrophoresis and SDS-PAGE, respectively. The RAPD was performed according to the protocol developed in this study. In extracts from head/thorax of males identified seven esterases and EST-5 called αβ-esterase and other esterases β-esterases. According to the nhibitor sensitivity ithe esterases were classified as EST-1 cholinesterase I, EST-2 and EST-5 carboxylesterases, EST-3, EST-4, EST-6 acetylesterase and EST-7 arylesterase. In the analysis of thermostability was observed that the EST-7 showed higher thermostability and EST-2 was the most sensitive esterase. In extracts of head / thorax of males were a higher number of peptides in extracts of females. The analysis of population genetics using RAPD marker, showed that there is great polymorphism. The populations analized are different, and may present a high genetic variability ancestor. The populations of Colorado City and Cidade Gaucha have been grouped as well as the populations of Umuarama and Tapejara, demonstrating that these populations have no barriers to crossing between breeders. Due to the high variability and small genetic distance values in this species of beetle is well-fitting to the region, being necessary the development of programs to control this pest.